The frequency of laryngeal involvement in lipoid proteinosis patients - Yukkaldiran, Ahmet; Aksoy, Mustafa; Yesilova, Yavuz; Demir, Mahmut; Iynen, Ismail; An, Isa; Tanrikulu, Osman (Annals of Medical Research, 2021)
None